Epilepsy in Onchocerca volvulus Sero-Positive Patients From Northern Uganda—Clinical, EEG and Brain Imaging Features - Ogwang, Rodney; Ningwa, Albert; Akun, Pamela; Bangirana, Paul; Anguzu, Ronald; Mazumder, Rajarshi; Salamon, Noriko; Henning, Oliver Johannes; Newton, Charles R.; Abbo, Catherine; Mwaka, Amos Deogratius; Marsh, Kevin; et al. (Frontiers in Neurology, 2021)
Globally, epilepsy is the most common chronic neurological disorder. The incidence in sub-Saharan Africa is 2-3 times higher than that in high income countries. Infection by Onchocerca volvulus may be an underlying risk factor for the high burden and based upon epidemiological associations, has been proposed to cause a group of disorders – Onchocerca associated epilepsies (OAE) like nodding syndrome (NS). To improve our understanding of the disease spectrum, we described the clinical, electroencephalographic (EEG) and magnetic resonance imaging (MRI) features of children with epilepsy and sero-positive for Onchocerca Volvulus or OAE other than nodding syndrome. Twenty-nine children and adolescents with non-nodding syndrome OAE in northern Uganda were enrolled. A diagnosis of OAE was made in patients with epilepsy and seizure onset after age 3 years, no reported exposure to perinatal severe febrile illness or traumatic brain injury, no syndromic epilepsy diagnosis and a positive Ov-16 ELISA test. Detailed clinical evaluation including psychiatric, diagnostic EEG, a diagnostic brain MRI (in 10 patients) and laboratory testing were performed. Twenty participants (69%) were male. The mean age was 15.9 (standard deviation [SD] 1.9) years while the mean age at seizure onset was 9.8 (SD 2.9) years. All reported normal early childhood development. The most common clinical presentation was a tonic-clonic seizure. The median number of seizures was 2 (IQR 1-4) in the previous month. No specific musculoskeletal changes, or cranial nerve palsies were reported, neither were any vision, hearing and speech difficulties observed. The interictal EEG was abnormal in the majority with slow wave background activity in 52% (15/29) while 41% (12/29) had focal epileptiform activity. The brain MRI showed mild to moderate cerebellar atrophy and varying degrees of atrophy of the frontal, parietal and occipital lobes. The clinical spectrum of epilepsies associated with Onchocerca may be broader than previously described and may include mild symptomatic epilepsies. In addition, focal onset tonic-clonic seizures, cortical and cerebellar atrophy may be important brain imaging and clinical features.